PERANAN PUSTAKAWAN DALAM MEWUJUDKAN PERPUSTAKAAN DIGITAL - Afrizal Afrizal (Maktabatuna, 2019)
A good library is a library that has been managed perfectly in accordance with library science and applies the latest technology, and is utilized by the library to its full potential. All information sought by users can already be found quickly and precisely. Because the library has provided all sources of information, and all collections have been digitalized perfectly. To realize the digitization library, it is very necessary that experts in the technology are needed. Librarians who always take part in the library are highly demanded for their role in realizing digital libraries.